Making sense of race in education : practices for change in difficult times - Heybach, Jessica A.; Fraser-Burgess, Sheron (Academy for Educational Studies book series., 2020)
"Making Sense of Race in Education: Practices for Change in Difficult Times takes a fresh look at the perennial issue of race in American schools. How do educators, in all settings, confront the issue of race with students and colleagues, given the contemporary backdrop of social movements for racial justice and change? How do educators affect change within their everyday classroom practices without fostering further alienation and discord? Although much has already been written about race and racism in school, this book addresses racial incidents directly and offers practical insights into how P-20 educators can transform these events alongside students and colleagues. Each chapter provides detailed analysis of curriculum, instruction, practices and pedagogical strategies for addressing race while at the same time wrestling with theoretical conceptions of race, justice, and fairness." --